A rational design of NixCoyP@C cocatalyst for enhanced overall water splitting based on g-C3N4 photocatalyst — the synergy of carbon-shell modification and bimetal modulation. Issue 3 (6th January 2022) - Zhang, Tingfeng; Lan, Xuefang; Wang, Lili; Shi, Jinsheng; Xiao, Kefeng
Abstract : Enhanced photocatalytic H2 evolution by bimetal cocatalyst of NiCoP@C. Abstract : Developing high-performance and low-cost cocatalysts is crucial to realize large-scale H2 production using solar energy. Herein, non-precious Ni x Co y –P@C core–shell nanoparticles (NPs) are synthesized as a high-active cocatalyst for photocatalytic water splitting. After coupling with g-C3 N4, H2 and O2 production achieved 485 and 240 μmol g −1 h −1 ; the half-reaction of H2 evolution achieved 4182 μmol g −1 h −1, comparable to 4552 μmol g −1 h −1 of Pt/g-C3 N4 . The carbon shell leads to the controlled core size of Ni x Co y –P NPs, leading to an interfacial contact with g-C3 N4, rapid electron transfer efficiency, and enhanced electron receiving capability of the catalyst. The carbon-shell and Ni x Co y –P NPs contribute to a significant synergy in promoting carrier separation and transfer efficiency. The Ni/Co ratio modulation in Ni x Co y –P NPs could optimize the work function of the cocatalyst for H2 evolution. Besides, carbon-shell introduces more pore structures and increases the surface area of the catalysts, which could provide more sites to receive electrons for H2 evolution. This work demonstrates the great potential of using high active and inexpensive Ni x Co y –P@C to replace expensive Pt for photocatalytic H2 evolution and open new avenues for optimizing cocatalyst with an excellent performance by bimetals modulation and carbon-shell coating.